Who benefits from active music engagement during cancer treatment? Associations of sociodemographic characteristics and risk factors with moderators of intervention effects - Holochwost, Steven J.; Harman, Elizabeth; Stegenga, Kristin; Jacob, Seethal A.; Robb, Sheri L. (Frontiers in Psychology, 2025)
Young children and their parents experience frequent and repeated exposure to potentially traumatic events during treatment for cancer. Active Music Engagement (AME) is a dyadic music therapy intervention that has been found to mitigate traumatic stress symptoms among parents who screened high for traumatic stress symptoms (TSS) and reported higher levels of child distress with cancer-related hospitalizations/treatment (child distress). The current study examined sociodemographic characteristics and risk factors that were associated with higher levels of parent TSS and child distress as a means to identify families that may benefit most from AME in the future. Data were collected from the parents (or guardians) of N =136 young children (Mage = 4.88 years, SD = 1.56 years, 44.1% female) who were undergoing treatment for cancer. Parents (or guardians) completed measures that captured child and respondent demographics as well as levels of parent TSS and child distress. A series of multivariable linear regression models revealed that poorer child health was associated with significantly higher levels of child distress and parent TSS, while more frequent participation in religious or spiritual practice were associated with lower levels of TSS. Higher levels of cumulative risk were associated with higher levels of child distress and parent TSS, but different, specific risk factors were more strongly associated with each of these outcomes: income-to-needs ratios below the federal poverty level (FPL) were associated with higher child distress, whereas single partner status and parental unemployment were associated with higher levels of parent TSS.